2022
DOI: 10.3390/cancers14225624
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic Breast Surgery versus Conservative Mastectomy in the Management of Large Ductal Carcinoma In Situ (DCIS): Surgical, Oncological, and Patient-Reported Outcomes

Abstract: Oncoplastic level II breast-conserving surgery (OPS2) allows for wider excisions than standard breast-conserving surgery, but the literature on this technique in the treatment of DCIS is scarce. This study compares OPS2 to conservative mastectomy (CM) in patients undergoing surgery for large DCIS. The clinical, radiological, surgical, and post-operative data of 147 patients who underwent either CM or OPS2 for large DCIS between 2007 and 2021 were retrospectively reviewed. The surgical, oncological, and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To support this result, we performed a Kaplan-Meier analysis of recurrence of this sub-group of patients and margin status, and no correlation between these two parameters was observed. Shaikh et al, in a recent analysis report, produced a similar result based on a more up-to-date sample of patients compared with a previous metaanalysis [7]. Such differences in the results could be justified by the implementation of digital and contrast enhancement mammography [23,24].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…To support this result, we performed a Kaplan-Meier analysis of recurrence of this sub-group of patients and margin status, and no correlation between these two parameters was observed. Shaikh et al, in a recent analysis report, produced a similar result based on a more up-to-date sample of patients compared with a previous metaanalysis [7]. Such differences in the results could be justified by the implementation of digital and contrast enhancement mammography [23,24].…”
Section: Discussionmentioning
confidence: 78%
“…Obtaining negative margins in DCIS could be difficult due to its presentations [6]. In situ lesions often present as vague masses, which cannot be clinically assessed by the physicians [7]. Nowadays, re-excision is the gold standard treatment whenever margins are positive or criteria are not met in DCIS [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of patient-reported outcomes (PROs) in the perioperative period of breast cancer has been reported [20][21][22]. However, few studies have focused on patients with metastatic or recurrent breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that women who underwent O-BCS had better sexual well-being and residual skin sensitivity compared to those who underwent mastectomy, despite the type of reconstruction ( 74 ). These findings suggest that preserving the breast tissue and improving breast appearance through oncoplastic techniques can have a positive impact on sexual well-being for breast cancer survivors ( 75 ). However, it is important to note that individual experiences may vary and additional support may still be needed.…”
Section: Qol Outcomesmentioning
confidence: 97%